2024
DOI: 10.1039/d3dt03557c
|View full text |Cite
|
Sign up to set email alerts
|

Insight into ferromagnetic interactions in CuII–LnIII dimers with a compartmental ligand

Anangamohan Panja,
Sagar Paul,
Eufemio Moreno-Pineda
et al.

Abstract: In the last two decades, efforts have been devoted to obtaining insight into the magnetic interactions between CuII and LnIII utilizing experimental and theoretical means. Experimentally, it has been observed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…In this context, previous experimental and theoretical studies have demonstrated that the incorporation of 3d-4f magnetic interactions represents a potent strategy for suppressing or eliminating QTM process. This is because 3d ions can impart stronger magnetic coupling and/or magnetic anisotropy, while 4f ions contribute significant single-ion magnetic anisotropy. The seminal work in the field of 3d-4f systems by Gatteschi et al unveiled a fairly strong Cu–Gd ferromagnetic exchange interaction, and finally after two decades, a tetranuclear Cu 2 II Tb 2 III complex has been reported that displayed SMM characteristics for the first time in the class of the 3d-4f system . Thereafter, a large number of SMMs with different nuclearities and topological structures have been reported, particularly those consisting of Cr III , Mn III/IV , Fe II/III , Co II , and Ni II ions. Among the various transition metal ions involved in the construction of 3d-4f complexes, the Co II - or Ni II -containing systems are quite advantageous as in addition to the usual ferromagnetic interaction between these 3d and 4f metal ions, leading to the large ground spin state, they may also contribute anisotropy to the 3d-4f clusters. ,, Consequently, a number of interesting 3d-4f SMMs with Co II or Ni II ions have been reported with varying nuclearity and topology. …”
Section: Introductionmentioning
confidence: 99%
“…In this context, previous experimental and theoretical studies have demonstrated that the incorporation of 3d-4f magnetic interactions represents a potent strategy for suppressing or eliminating QTM process. This is because 3d ions can impart stronger magnetic coupling and/or magnetic anisotropy, while 4f ions contribute significant single-ion magnetic anisotropy. The seminal work in the field of 3d-4f systems by Gatteschi et al unveiled a fairly strong Cu–Gd ferromagnetic exchange interaction, and finally after two decades, a tetranuclear Cu 2 II Tb 2 III complex has been reported that displayed SMM characteristics for the first time in the class of the 3d-4f system . Thereafter, a large number of SMMs with different nuclearities and topological structures have been reported, particularly those consisting of Cr III , Mn III/IV , Fe II/III , Co II , and Ni II ions. Among the various transition metal ions involved in the construction of 3d-4f complexes, the Co II - or Ni II -containing systems are quite advantageous as in addition to the usual ferromagnetic interaction between these 3d and 4f metal ions, leading to the large ground spin state, they may also contribute anisotropy to the 3d-4f clusters. ,, Consequently, a number of interesting 3d-4f SMMs with Co II or Ni II ions have been reported with varying nuclearity and topology. …”
Section: Introductionmentioning
confidence: 99%